METHODOLOGY FOR IMPROVING PEDAGOGICAL MECHANISMS OF THE EDUCATIONAL PROCESS IN DEVELOPING LANGUAGE COMPETENCIES OF FUTURE TEACHERS - Khasanova Madina (Ta'lim innovatsiyasi va integratsiyasi, 2026)
This  article  highlights  the  issues  related  to  improving  the  pedagogical mechanisms  used  in  the  process  of  developing  language  competencies  of  future teachers.  The  effectiveness  of  modern  language-teaching  technologies,  the competency-based approach, the use of digital resources, and interactive methods is scientifically analyzed. Additionally, methodical recommendations aimed at enhancing language competencies are presented.